Algae as a Source of Bioactive Compounds to Prevent the Development of Type 2 Diabetes Mellitus - Popović-Djordjević, Jelena B.; Katanić Stanković, Jelena S.; Mihailović, Vladimir; Pereira, Antia G.; Garcia-Oliveira, Paula; Prieto, Miguel A.; Simal-Gandara, Jesus (Current Medicinal Chemistry, 2021)
Type 2 diabetes mellitus is a complicated metabolic disorder characterized by hyperglycemia and glucose intolerance. It is considered a new pandemic and its control involves numerous challenges. Although many of the measures are based on improving life habits, diet is also of vital importance due to bioactive compounds present in food. In this regard, several raw materials have been investigated whose bioactivities seem to slow the progression of this disease. Within these matrices, there are algae of importance, such as brown algae, showing to have beneficial effects on glycemic control. These pieces of evidence are increasing every day due to the development of cell or animal models, which lead to the conclusion that bioactive compounds may have direct effects on decreasing hyperglycemia, enhancing insulin secretion and preventing the formation of amyloid plaques.
Keywords: Diabetes mellitus